Theory generation from literature reviews: A methodological guidance - Tsiotsou, R. H.; Koles, B.; Paul, J.; Loureiro, S. M. C. (International Journal of Consumer Studies, 2022)
This article aims to assist researchers in navigating the path to theory creation by investigating how they might build theory through literature reviews. In particular, we propose and elaborate upon the Theory Generation from Literature Review (TGLR) process, capturing different methods and techniques to be applied depending on the level of development and saturation characterizing the focal area of inquiry. In the second part of the article, we briefly present the 21 articles conducting systematic literature reviews on consumer research topics selected for this special issue in IJCS.